1994
DOI: 10.1183/09031936.94.07101825
|View full text |Cite
|
Sign up to set email alerts
|

Time-limited protective effect of inhaled frusemide against aspirin-induced bronchoconstriction in aspirin-sensitive asthmatics

Abstract: Inhaled frusemide effectively prevents the bronchial obstructive response to allergens and to a number of nonallergic stimuli. In most of the experimental models in which it has been tested, the protective effect of frusemide has been evaluated for only a short time after administration. In aspirin-sensitive patients, acetylsalicylic acid causes an asthmatic reaction which typically lasts for 2 h or more after exposure. We investigated the presence and duration of the protective effect of inhaled frusemide aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Sestini et al reported that the duration of the effect of inhaled furosemide in aspirin-in-duced bronchial asthma was approximately 2 hours. 11 However, in another report, furosemide had protective effect against allergen-induced asthma up to 12 hours after inhalation. 7 We administered furosemide therapy using the same schedule as the prior orciprenaline therapy, which was a four times a day.…”
Section: Discussionmentioning
confidence: 93%
“…Sestini et al reported that the duration of the effect of inhaled furosemide in aspirin-in-duced bronchial asthma was approximately 2 hours. 11 However, in another report, furosemide had protective effect against allergen-induced asthma up to 12 hours after inhalation. 7 We administered furosemide therapy using the same schedule as the prior orciprenaline therapy, which was a four times a day.…”
Section: Discussionmentioning
confidence: 93%
“…Obviously, a double‐blind design was possible only for controls and patients with ATA. Patients with AIA received the saline challenge first and a single dose of L‐ASA corresponding to the last cumulative dose that caused a decrease in FEV 1 of 20% compared with baseline in the preliminary test (15). In controls and in patients with ATA a single 128 mg dose of L‐ASA was used for the L‐ASA inhalation challenge.…”
Section: Methodsmentioning
confidence: 99%
“…13 Aspirin can induce asthma in some patients through the inhibition of cyclooxygenase. 37,38 Nebulized furosemide has been shown to provide protection against aspirin-induced bronchoconstriction in two randomized controlled studies. 37,38 When patients took indomethacin, a known inhibitor of cyclooxygenase (50 mg), three times a day for three days prior to the test, the effects of nebulized furosemide were significantly reduced.…”
Section: Asthmamentioning
confidence: 99%